2010
DOI: 10.1088/0031-8949/82/04/045606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser irradiation on the mechanical response of polycrystalline titanium

Abstract: The effects of laser treatment on the mechanical response of polycrystalline titanium (99.99%) have been investigated using the laser gas nitriding technique. Samples were subjected to irradiation by a 532 nm pulsed Nd:YAG laser for 100–400 shots. Laser pulses of energy 370 mJ with 10 Hz repetition rate were used to irradiate the surface of specimens and to activate the reaction between the irradiated surface and nitrogen. The effects of multiple laser pulses on the microstructure, yield stress (YS), ultimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Since the voltage controls the welding energy, an increase of voltage leads to a greater welding depth [4][5][6][7][8][9][10][11][12][13][14][15]17]. Chai and Chou [18] reported that pulse duration is not a significant factor to affect the Ultimate Tensile Strength (UTS) or the Yield Strength (YS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the voltage controls the welding energy, an increase of voltage leads to a greater welding depth [4][5][6][7][8][9][10][11][12][13][14][15]17]. Chai and Chou [18] reported that pulse duration is not a significant factor to affect the Ultimate Tensile Strength (UTS) or the Yield Strength (YS).…”
Section: Discussionmentioning
confidence: 99%
“…Laser beams are widely used for surface modification [4][5][6][7][8][9][10][11] because specific thermal characteristics induced by laser irradiation can generate specific microstructures including metastable phases and nano-crystalline grains. The convective fluxes and hydrodynamic instabilities inside the irradiated surface layers contribute to the heat transport to mix the ambient gas and molten metal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the content of oxygen from 4.91 wt.% to a value of 21.52 wt.% is observed in case of deionized water, whereas less diffusion of oxygen (15.55 wt.%) but increase in content of carbon from 2.82 to 3.36 wt.% is observed in case of ethanol. Multipulse irradiation induced heating of Zr causes efficient diffusion of atomic oxygen/carbon into the target surface; therefore, oxides and carbides are formed [26]. For deionized water (Figure 5a), Raman peaks identified at 320, 337 cm −1 represents the Zr─Zr bond.…”
Section: Xrd Patterns Displayed Inmentioning
confidence: 99%
“…For 2000 number of laser pulses, material segregates into distinct grains with average grain size of 3.26 μm and much wider grain boundaries (Figure 7e). Laser-induced heating and cooling, the temperature gradient, and laser-induced residual stresses are responsible for growth of such grains [26]. When the laser pulse is over, the molten material generated by fast heating is supercooled and acts as an effective heat sink that quickly removes any released latent heat and causes the crystal growth.…”
Section: Effect On Surface Morphologymentioning
confidence: 99%